2011
DOI: 10.4161/cib.15222
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic influences on multisensory integration

Abstract: In everyday life our brain often receives information about events and objects in the real world via several sensory modalities, because natural objects often stimulate more than one sense. These different types of information are processed in our brain along different sensory-specific pathways, but are finally integrated into a unified percept. During the last years, studies provided compelling evidence that the neural basis of multisensory integration is not restricted to higher association areas of the cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 57 publications
(63 reference statements)
2
74
0
1
Order By: Relevance
“…For example, the feline suprageniculate nucleus of the posterior thalamus contains many unimodal cells (responding only to one sensory modality) but 20 % bimodal and trimodal cells, responding to various combinations of visual, auditory, somatosensory and nociceptive information (Benedek et al, 1997). Similar results were found for the pulvinar nucleus of the thalamus (Tyll et al, 2011). Several studies have further shown that at the functional level, thalamic structures are involved in multisensory integration processes (Tyll et al, 2011).…”
Section: Integration Of Pain With Other Types Of Informationsupporting
confidence: 70%
See 2 more Smart Citations
“…For example, the feline suprageniculate nucleus of the posterior thalamus contains many unimodal cells (responding only to one sensory modality) but 20 % bimodal and trimodal cells, responding to various combinations of visual, auditory, somatosensory and nociceptive information (Benedek et al, 1997). Similar results were found for the pulvinar nucleus of the thalamus (Tyll et al, 2011). Several studies have further shown that at the functional level, thalamic structures are involved in multisensory integration processes (Tyll et al, 2011).…”
Section: Integration Of Pain With Other Types Of Informationsupporting
confidence: 70%
“…Several studies have further shown that at the functional level, thalamic structures are involved in multisensory integration processes (Tyll et al, 2011). For example, humans were more accurate in classifying emotional stimuli when these were presented audiovisually, compared to when they were presented by auditory or visual stimuli separately, and this was associated with increased activity in the thalamus (Tyll et al, 2011).…”
Section: Integration Of Pain With Other Types Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this has recently been shown within SL using the McGurk effect (see Glossary) in a cross-modal segmentation study [32]. More generally, perception of the world routinely involves multisensory integration (e.g., [33]), occurring at both low levels (i.e., the thalamus, [34]; the dorsal cochlear nucleus, [35]) and higher levels of cortical processing (e.g., anterior temporal poles; [36]). Critically, however, each of these multimodal areas would be subject to its own distinct set of constraints, which would not necessarily be the same as those from the unimodal regions that feed into it or to the constraints in other multimodal areas.…”
Section: Towards a Mechanistic Model Of Slmentioning
confidence: 91%
“…The authors also suggested different levels of multisensory divergence in the opposite direction to information flow. Other researchers have considered several possible neural mechanisms for multisensory interaction in sensory-specific cortices 24,26,27) . The first is feedback effects from multisensory convergence zones in higher association regions to sensory specific regions.…”
Section: Very Early Multisensory Integrationmentioning
confidence: 99%